"Naked" Magnetically Recyclable Mesoporous Au–γ‐Fe2O3 Nanocrystal Clusters: A Highly Integrated Catalyst System. (16th January 2017) - Shang, Lu; Liang, Yunhui; Li, Mengzhu; Waterhouse, Geoffrey I. N.; Tang, Pei; Ma, Ding; Wu, Li‐Zhu; Tung, Chen‐Ho; Zhang, Tierui
Abstract : Naked magnetically recyclable mesoporous Au–γ‐Fe2 O3 clusters, combining the inherent magnetic properties of γ‐Fe2 O3 and the high catalytic activity of Au nanoparticles (NPs), are successfully synthesized. Hydrophobic Au–Fe3 O4 dimers are first self‐assembled to form sub‐micrometer‐sized Au–Fe3 O4 clusters. The Au–Fe3 O4 clusters are then coated with silica, calcined at 550 °C, and finally alkali treated to dissolve the silica shell, yielding naked‐Au–γ‐Fe2 O3 clusters containing Au NPs of size 5–8 nm. The silica protection strategy serves to preserve the mesoporous structure of the clusters, inhibit the phase transformation from γ‐Fe2 O3 to α‐Fe2 O3, and prevent cluster aggregation during the synthesis. For the reduction of p ‐nitrophenol by NaBH4, the activity of the naked‐Au–γ‐Fe2 O3 clusters is ≈22 times higher than that of self‐assembled Au–Fe3 O4 clusters. Moreover, the naked‐Au–γ‐Fe2 O3 clusters display vastly superior activity for CO oxidation compared with carbon‐supported Au–γ‐Fe2 O3 dimers, due to the intimate interfacial contact between Au and γ‐Fe2 O3 in the clusters. Following reaction, the naked‐Au–γ‐Fe2 O3 clusters can easily be recovered magnetically and reused in different applications, adding to their versatility. Results suggest that naked‐Au–γ‐Fe2 O3 clusters are a very promising catalytic platform affording high activity. The strategy developed here can easily be adapted to other metal NP–iron oxide systems. Abstract : "Naked" magnetically recyclable mesoporous Au– γ‐Fe2 O3 clusters are successfully fabricated by combining a self‐assembly method with a silica‐protected calcination strategy. On account of their clean surfaces, small Au nanoparticle size, the inherent magnetism of γ‐Fe2 O3, and the excellent interfacial contact between the Au and γ‐Fe2 O3 nanoparticles, the clusters show outstanding catalytic performance in the reduction of 4‐nitrophenol and enhanced performance in the catalytic oxidation of CO.